Nephroprotective effect of extract Etlingera elatior (Jack) R.M. Smith on CCl4-induced nephrotoxicity in rats - Adryan Fristiohady; Wahyuni Wahyuni; Muhammad Ilyas Y; Mentarry Bafadal; La Ode Muhammad Julian Purnama; Firasmi Sangadji; Muhammad Hajrul Malaka; Fadhliyah Malik; Junli Hong; Agung Wibawa Mahatva Yodha; I Sahidin (Current Research on Bioscences and Biotechnology, 2020)
Reactive oxidative stress (ROS) can lead to cell damage, and one of them is the kidney's cell. Etlingera elatior (Jack) R.M. Smith can be utilized as an agent that can protect the cell from ROS. This study aimed to investigate the protective effect of E. elatior fruit on the kidney's cell. We used experimental animals which were treated with Na-CMC (Group I), Na-CMC (Group II), the extracts of E. elatior fruit 200, 300, 400 mg/kg BW for Group III, IV, and V, respectively, for seven days. The blood was collected after treatment. At day 8, group I, III, IV, and V were induced by CCl4. At day 9, blood was collected and the kidneys were harvested for histopathology analysis. Blood collected were measured for albumin, total protein, urea and creatinine levels. After treatment, albumin and total protein showed no increased levels; urea decreased at doses of 200, 300, and 400 mg/kg BW, respectively, and creatinine levels only decreased at the dose of 400 mg/kg BW (p<0.05). The dose of 200 and 300 mg/kg BW showed protecting effects in the tubular cells of renal. Therefore, the ethanol extract of E. elatior showed a nephroprotective effect by normalizing the urea and creatinine levels of rats and protecting tubular cells of renal.